First-time fathers' experiences during their transition to parenthood: A study of Korean fathers - Nan Iee Noh (Korean Academy of Child Health Nursing, 2021)
Purpose This study was conducted to explore first-time fathers' experiences during their transition to parenthood in South Korea. Methods Data were collected from September 2019 to February 2020 through in-depth interviews that were conducted individually with 12 participants. First-time fathers with children under 2 months of age were recruited. Verbatim transcripts were analyzed using Colaizzi's phenomenological method. Results Four theme clusters were identified: Preparing to become a father, challenges of becoming a father, motivation to foster familial bonds, and acknowledgement of fatherhood. Conclusion These findings suggest that Korean first-time fathers prepared to practice parenthood through prenatal education, taegyo, and feeling bonds with their new baby. They recognized their identity as fathers and experienced self-growth. These results would be beneficial for health professionals in developing perinatal care programs, and the results provide basic data for studies on fathers and families during the transition to parenthood.